Carcinoma gástrico en el perro: localización endoscópica y aspecto macroscópico - García-sancho, Mercedes; Rodríguez-franco, Fernando; Carrasco, Violeta; Canfrán, Susana; Sainz, Ángel; Rodríguez , Antonio (Revista Complutense de Ciencias Veterinarias, 2009)
The aim of this paper is to study endoscopic localizations and macroscopic appearance of canine gastric carcinoma. Clinical histories of seventeen dogs were analyzed. All cases were diagnosed of gastric carcinoma by Upper Digestive Endoscopy and Biopsy. The results of this study show that pyloric antrum and lesser curvature are the most frequent locations of canine gastric carcinoma: in 64.7% of the cases pyloric antrum was affected, even though some of them were extended to other zones of the stomach as well; on the other hand, 47% of the studied cases affected the lesser curvature, but only 11.8% were limited to that location.